Phase Pure Synthesis and Morphology Dependent Magnetization in Mn Doped ZnO Nanostructures. (19th May 2014) - Saleem, Murtaza; Atiq, Shahid; Ramay, Shahid M.; Mahmood, Asif; Siddiqi, Saadat A.; Shar, Muhammad Ali
Abstract : Zn0.95 Mn0.05 O nanostructures were synthesized using sol gel derived autocombustion technique. As-burnt samples were thermally annealed at different temperatures (400, 600, and 800°C) for 8 hours to investigate their effect on structural morphology and magnetic behavior. X-ray diffraction and scanning electron microscopic studies demonstrated the improvement in crystallinity of phase pure wurtzite structure of Mn doped ZnO with variation of annealing temperature. Energy dispersive X-ray elemental compositional analysis confirmed the exact nominal compositions of the reactants. Electrical resistivity measurements were performed with variation in temperature, which depicted the semiconducting nature similar to parent ZnO after 5 at% Mn doping. Magnetic measurements by superconducting quantum interference device detected an enhanced trend of ferromagnetic interactions in thermally annealed compositions attributed to the improved structural morphology and crystalline refinement process.